THE INFLUENCE OF COMMUNITY BEHAVIOR ON THE LOWER VISITS OF INPATIENTS AT RS.TIARA KASIH SEJATI, PEMATANG SIANTAR CITY, NORTH SUMATRA - Yenni Hastita; Desideria Yosepha Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Based on BOR statistical data in 2020 and 2021 at Tiara Kasih Sejati Hospital, it was found that the number was still below the ideal, the low number of inpatient visits at Tiara Kasih Sejati Hospital was probably influenced by cognitive factors, environmental factors and behavioral factors, for that purpose research was conducted to determine the effect of behavior community towards the low number of inpatient visits at the hospital. Tiara Kasih Sejati, Pematangsiantar Municipality, North Sumatra. This research was conducted using an analytic survey with a cross sectional study approach. The results of the study for cognitive with p value = 0.002 there was a cognitive relationship with the low number of inpatient visits at the hospital. Tiara Kasih Sejati, Pematangsiantar Municipality, North Sumatra, for the environment with a p value = 0.004 there was a relationship between the environment and the low number of inpatient visits at the hospital. Tiara Kasih Sejati, Pematangsiantar Municipality, North Sumatra, for behavior with a p value = 0.002, there was a behavioral relationship with low inpatient visits at the hospital. Tiara Kasih Sejati, Pematangsiantar Municipality, North Sumatra. The conclusion is there is an influence of community behavior on the low number of inpatient visits at the hospital. Tiara Kasih Sejati, Pematangsiantar Municipality, North Sumatra. Where the most dominant factor is the cognitive factor compared to environmental factors and behavioral factors.